THE INFLUENCE OF CORPORATE SOCIAL RESPONSIBILITY ON MALAYSIA AIRLINES INVESTMENT DECISIONS - Melia Santi; Nunik Nurmalasari (STIESA Press, 2020)
The aims of this study is to empirically prove the influence of Corporate Social Responsibility on investment decisions in Malaysian airlines. the results of this study can be used as information for investors when buying shares in a company when investing. The analytical tool used in this study uses a simple linear regression analysis method through tests of normality, autocorrelation, t test and coefficient of determination. The population in this study are all AirAsia BHD financial statements from the IPO to the present. The sample used in this study is AirAsia's BHD financial statements starting from 2014-2018. The data used in this study are secondary data, namely AirAsia BHD financial statements and information relating to the company through the website. Based on the results of the study found that disclosure of Corporate Social Responsibility has no effect on investment decisions.